Optically pumped ZnCdSe-ZnSe quantum wells - DONEGAN, JOHN; HEGARTY, JOHN (My University, 1996)
We have measured the gain spectrum of an optically pumped 40A ZnCdSe-ZnSe multiple quantum well. Our calculation, which includes many body effects such as Coulomb enhancement and spectral broadening due to carrier scattering, gives excellent agreement with the experimental gain measurements. We then show the importance of the inclusion of the Coulomb enhancement for the calculation of optical gain when predicting laser threshold currents. This is emphasised by using our gain calculation as a basis to theoretically optimise a simple ZnCdSe-ZnSe quantum well laser structure incorporating the leakage current over the p-type cladding.
Proceedings of SPIE
Physics and Simulation of Optoelectronic Devices IV
PUBLISHED
San Jose, CA, USA
Keywords: semiconductor laser diodes; Il-VI; optical gain; many body effects